Cybersecurity Challenges in Management Information Systems in the Hybrid Work Era - Rayyan Firdaus; Apni Gustiari Tanjung; Dea Lorenza (Jurnal Intelek Dan Cendikiawan Nusantara, 2026)
The adoption of the hybrid work model provides high operational flexibility for organizations, but the other hand, it expands vulnerability gaps within Management Information Systems (MIS). This study aims to identify the main cybersecurity challenges faced by MIS in the hybrid work era and to formulate effective mitigation strategies. Using a qualitative descriptive approach based on a literature review, this study finds that the shattering of network perimeters, the insecure use of personal devices (BYOD), and the rise of phishing attacks are the most dominant cyber threats. The analysis indicates that traditional security models are no longer sufficient to protect corporate information assets. As a solution, this article recommends the implementation of a Zero Trust Security architecture, the activation of Multi-Factor Authentication (MFA), end-to-end data encryption, and the strengthening of a cyber-aware culture among employees. The implementation of these strategies is expected to maintain the integrity of MIS without sacrificing employee work flexibility.